Automation of quality control at oil factories (improvement of oil quality). - Asranov H.K; Abdusalomov M.B; Tojiboyev H. Sh (Zien Journals, 2023)
In this study, a model of automation of the quality control system of the organization of the construction of highly dangerous and technically complex objects was developed. The model uses the original and updated databases of general and special work logs, as well as the database of attestationpermitting documents and the established connections between them.
Keywords: quality control; quality control automation; construction organization